PENJADWALAN PRODUKSI DI PT SAI APPAREL INDUSTRIES SEMARANG - Asmoro Dwi Nugroho; Firman Ardiansyah Ekoanindiyo (Jurnal Ilmiah Dinamika Teknik, 2017)
One of the problems in the production system is to arrange job scheduling (jobs) so that consumer needs can be fulfilled. To be able to overcome the problems and achieve that goal is to do the production scheduling. Production process scheduling can reduce idle time on production units and minimize work in proces (Rosnani, Ginting 2009: 6). Of the five Hall's production, not only produce one type of product only, each hall produces according to whatever request goes into the company in one month. In each production hall there is a line - line of successive work resulting in the product of jeans, and other products demanded by consumers / buyers. In doing its production PT. Sai Apparel Industries uses 6 working days a week, with 3 shifts and one shift for 8 hours. If within the time specified in the production scheduling is deemed not sufficient target, it will be done overtime to meet those targets. The whole production process at PT. Sai Apparel Industries depends on buyer order, then from the ordering data is made scheduling for daily production to fulfill the request.Keywords: Scheduling, Jobs (Jobs), Consumer Demand